Determinants of thymotropism in Kaplan radiation leukemia virus and nucleotide sequence of its envelope region. - Poliquin, L (1992)
Radiation leukemia viruses (RadLVs) are a group of murine leukemia viruses which are induced by radiation and cause T-cell leukemia. Viral clones isolated from the BL/VL3 lymphoid cell line derived from a thymoma show variable tropism and leukemogenic potential. We have constructed chimeric viruses by in vitro recombination between two viruses, a RadLV that is thymotropic and an endogenous ecotropic virus that is nonthymotropic. We show here that, in contrast to thymotropism determinants identified previously, which lie in the long terminal repeat (LTR), it is the envelope region that is responsible for the thymotropism of BL/VL3 RadLV. The nonthymotropic virus which we have rendered thymotropic by transfer of the env region of RadLV in the present study has been shown previously to become thymotropic when the LTR of another thymotropic virus is inserted in its genome. Thus, the LTR and envelope gene may be involved in complementary action to lead to thymotropism.